2014
DOI: 10.1007/s11095-014-1553-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of oil-in-Water Nanoemulsion Polyethylene Glycol Surface Density on Intracellular Stability, Pharmacokinetics, and Biodistribution in Tumor Bearing Mice

Abstract: Optimal PEG surface density of lipid-based nanoparticles for tumor targeting was found to be below 10 mol%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…Preclinical studies have shown that BBR has a very limited oral bioavailability (BA) (< 5% in plasma), largely due to its poor aqueous solubility, combined with low gastrointestinal absorption, and rapid metabolism [ 48 ]. However, novel self-nanoemulsion system is an emerging area of science and includes material application on the nanometre scale in various domains, including biology, chemistry, medicine, and engineering [ 49 ]. It is likely to improve the solubility stability and selectivity of drugs, improving the permeability of drugs while treating solid tumours through the enhanced permeability and retention effect, even for the blood brain barrier, which is high correlated with leukemia metastasis of the bone borrow [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies have shown that BBR has a very limited oral bioavailability (BA) (< 5% in plasma), largely due to its poor aqueous solubility, combined with low gastrointestinal absorption, and rapid metabolism [ 48 ]. However, novel self-nanoemulsion system is an emerging area of science and includes material application on the nanometre scale in various domains, including biology, chemistry, medicine, and engineering [ 49 ]. It is likely to improve the solubility stability and selectivity of drugs, improving the permeability of drugs while treating solid tumours through the enhanced permeability and retention effect, even for the blood brain barrier, which is high correlated with leukemia metastasis of the bone borrow [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, only a few studies have investigated how to prolong the half-life of PEGylated NEs [ 30 , 51 , 52 ]. Cheng et al studied how different molecular weights and different concentrations of lipid–PEG affected NE size but did not analyze their pharmacokinetic profiles [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…PEGylation of liposomes [ 27 ], micelles [ 28 ], and nanoparticles [ 29 ] has been widely investigated, but only a few works have focused on NE surface modification with PEG. Hak et al [ 30 ] studied the impact of PEG surface density on NE half-life by blood sampling at different time points after administration in mice. Here, the effect of NE surface modification by PEG layers of different molecular weights (PEG 2000 and/or PEG 3400 ) on liver uptake was studied by dynamic MRI.…”
Section: Introductionmentioning
confidence: 99%
“…Target, distribution, and metabolism of contrast agents in vivo can be observed by small animals living optical imaging [ 31 ]. The tendency of the accumulated fluorescence at tumor site consistent with the tumor ultrasound imaging suggested that the NPs remained at the tumor tissue.…”
Section: Discussionmentioning
confidence: 99%